Donkey milk supplementation alleviates renal fibrosis of chronic kidney disease by enhancing anti-inflammatory ability - Cui Huimin; Wang Peng; Chen Man; Lin Hong; Zhao Yuxin; Pu Zhiyu; Yang Jianjun (Journal of Dairy Science)
ABSTRACT: Donkey milk, rich in essential nutrients, is not only able to meet the nutritional needs of patients with chronic kidney disease (CKD) according to the National Kidney Foundation's Kidney Disease Outcomes Quality Initiative Clinical Practice Guideline for Nutrition in CKD, but also has strong anti-inflammatory properties. Inflammation is the main driving force of renal fibrosis, which directly determines renal function in CKD. However, the impact of donkey milk on CKD and the underlying mechanisms remain unclear. We hypothesized that donkey milk supplementation could enhance anti-inflammatory abilities in individuals with CKD, thereby inhibiting renal fibrosis and improving renal function. Therefore, we investigated the influence of a 6-wk treatment with donkey milk on unilateral ureteral ligation–induced CKD rats. The results demonstrated that the level of miR-223-3p was decreased in the kidneys of CKD rats compared with normal rats. However, donkey milk supplementation activated miR-223-3p, thereby inhibiting the expression of inhibitor of kappa-B kinase (IKKα) and nuclear factor kappa-B (NF-κB) proteins. Consequently, the expression of inflammatory factors such as monocyte chemotactic protein-1 (MCP-1) and IL-6 was suppressed, leading to reduced aggregations of macrophages in the kidney and decreased transforming growth factor β1 (TGF-β1) expression. Ultimately, renal fibrosis was inhibited, which was confirmed by decreased collagen type I α 1 (COL1A1) mRNA, thereby the renal function of CKD rats was improved. These results indicate that miR-223-3p may be another potential therapeutic target for CKD. Moreover, the contribution of donkey milk to alleviating the inflammatory response and renal fibrosis of CKD is obvious, indicating that donkey milk may be a new functional food for CKD patients to promote health.